An m6A-YTH Module Controls Developmental Timing and Morphogenesis in Arabidopsis. Issue 5 (11th April 2018) - Arribas-Hernández, Laura; Bressendorff, Simon; Hansen, Mathias Henning; Poulsen, Christian; Erdmann, Susanne; Brodersen, Peter
Abstract : The N6 -methyladenosine RNA binding proteins ECT2, ECT3, and ECT4 are required for the correct timing of leaf formation and correct leaf and trichome morphogenesis. Abstract: Methylation of N6 -adenosine (m 6 A) in mRNA is an important posttranscriptional gene regulatory mechanism in eukaryotes. m 6 A provides a binding site for effector proteins ("readers") that influence pre-mRNA splicing, mRNA degradation, or translational efficiency. YT521-B homology (YTH) domain proteins are important m 6 A readers with established functions in animals. Plants contain more YTH domain proteins than other eukaryotes, but their biological importance remains unknown. Here, we show that the cytoplasmic Arabidopsis thaliana YTH domain proteins EVOLUTIONARILY CONSERVED C-TERMINAL REGION2/3 (ECT2/3) are required for the correct timing of leaf formation and for normal leaf morphology. These functions depend fully on intact m 6 A binding sites of ECT2 and ECT3, indicating that they function as m 6 A readers. Mutation of the close ECT2 homolog, ECT4, enhances the delayed leaf emergence and leaf morphology defects of ect2/ect3 mutants, and all three ECT proteins are expressed at leaf formation sites in the shoot apex of young seedlings and in the division zone of developing leaves. ECT2 and ECT3 are also highly expressed at early stages of trichome development and are required for trichome morphology, as previously reported for m 6 A itself. Overall, our study establishes the relevance of a cytoplasmic m 6 A-YTH regulatory module in the timing and execution of plant organogenesis.